Work Engagement, Psychological Capital, and Employee Performance: The Mediating Role of Employee Well-Being in the Banking Industry - Resty Ismawanti; Imas Komariyah; Yudi Wahyudin Suwandi (AIBPM Publisher, 2025)
The banking industry increasingly requires employees who can sustain performance amid digital transformation, service pressure, and stricter operational targets. This study examines the influence of work engagement and psychological capital on employee performance, with employee well-being as a mediating variable at PT Bank Tabungan Negara (Persero) Tbk. A quantitative explanatory design was applied using survey data from 64 employees selected through simple random sampling. Data were collected using a structured five-point Likert questionnaire and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, and Sobel mediation testing using SPSS. The results show that work engagement significantly affects employee well-being (b = 0.312, p = 0.001) and employee performance (b = 0.298, p = 0.001). Psychological capital also significantly affects employee well-being (b = 0.298, p = 0.002) and employee performance (b = 0.276, p = 0.002). Employee well-being significantly improves employee performance (b = 0.421, p 0.001) and partially mediates both relationships. These findings emphasize that employee performance can be strengthened by developing engagement, psychological capital, and workplace well-being as integrated human resource strategies.